Live Birth Resulting from the Direct Warming and Direct Rehydration of Vitrified Human Blastocyst in Embryo Culture Medium: A Pilot Study - David Yiu Leung Chan; Murong Xu; Waner Wu; Ka Kei Fung; Linyao Zhang; Hoi Ming Wan; Carol Pui Shan Chan; Jacqueline Pui Wah Chung (Fertility & Reproduction)
Background: Frozen embryo transfer (FET) has been a routine assisted reproductive technology (ART) procedure since the first FET by slow freezing. It is estimated that more than 2 million FET cycles are performed worldwide each year. The stepwise removal of cytotoxic cryoprotectants and rehydration in serial osmotic solutions has been a fundamental principle, but the entire process is time-consuming and labor-intensive. Methods: A two-phase study was performed. In Phase 1 (technical validation), four culture media and phosphate-buffered saline (PBS)-only control with specific osmolality (270 ± 10 mOsm/KG) were used. Survival rates were determined by embryo movement and re-expansion under time-lapse imaging. The technical compatibility of repeated direct warming and repeated biopsies for preimplantation genetic tests was investigated. In Phase 2 (clinical application), 20 and 76 patients were recruited for direct and conventional warming. Cost-effectiveness analyses were performed. Results: In Phase 1, all culture media supported 100% survival rates ([Formula: see text] = 52), even in PBS ([Formula: see text] = 11). Revived blastocysts could re-expand as a conventional method. Directly rehydrated and warmed blastocysts in culture medium also survived from direct warming, trophectoderm biopsy, second vitrification, and second direct warming with the second biopsy, indicating compatibilities with conventional PGT procedures ([Formula: see text] = 13). In Phase 2, nonsignificant but higher implantation rates and clinical pregnancy rates were obtained from direct warming compared with conventional warming (61.9% vs. 38.5%, 60.0% vs. 39.5%), leading to healthy live births (LBs) (45% vs. 36.8%). Miscarriage rates were also comparable (three vs. two incidences). Cost-effectiveness analyses showed that direct warming could save 42% in consumable costs and 90% in labor hours. Conclusions: Current results showed that direct warming/rehydration is a feasible way, and gradual cryoprotectant removal and rehydration were unnecessary for human blastocyst warming survival. In this small sample-size pilot study, direct-warmed blastocysts supported all clinical outcomes equivalent to conventional procedures with saved time and money. Further multicenter clinical trials are needed to provide convincing resolutions on the direct warming and rehydration of human blastocysts.